2017
DOI: 10.1371/journal.pone.0188980
|View full text |Cite
|
Sign up to set email alerts
|

A unique plasma microRNA profile defines type 2 diabetes progression

Abstract: A major unmet medical need to better manage Type 2 Diabetes (T2D) is the accurate disease prediction in subjects who show glucose dysmetabolism, but are not yet diagnosed as diabetic. We investigated the possibility to predict/monitor the progression to T2D in these subjects by retrospectively quantifying blood circulating microRNAs in plasma of subjects with i) normal glucose tolerance (NGT, n = 9); ii) impaired glucose tolerance (IGT, n = 9), divided into non-progressors (NP, n = 5) and progressors (P, n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 38 publications
3
72
2
Order By: Relevance
“…Then, the relative level of miR-122 was found to be increased significantly, and that of IGF-1R protein, conversely, decreased in the liver of DM rats. Recent studies have indicated that accentuated miRNA dysregulation was found in impaired glucose tolerance and diabetes subjects with an increased level of miR-122 (de Candia et al, 2017;Ye et al, 2018). These previous studies and our in vivo data suggest that miR-122 may be involved in T2D and hepatic IR.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Then, the relative level of miR-122 was found to be increased significantly, and that of IGF-1R protein, conversely, decreased in the liver of DM rats. Recent studies have indicated that accentuated miRNA dysregulation was found in impaired glucose tolerance and diabetes subjects with an increased level of miR-122 (de Candia et al, 2017;Ye et al, 2018). These previous studies and our in vivo data suggest that miR-122 may be involved in T2D and hepatic IR.…”
Section: Discussionsupporting
confidence: 81%
“…(C) miR-122 relative expression. Recent studies have indicated that accentuated miRNA dysregulation was found in impaired glucose tolerance and diabetes subjects with an increased level of miR-122 (de Candia et al, 2017;Ye et al, 2018). Data are presented as the mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current work, we first investigated the expression of miRNA 342 amongst T2D patients, CAD patients (with its subtypes), and T2D with CAD (with its subtypes), where its expression was significantly upregulated in all the groups studied, especially those suffering from T2D with CAD clots, when compared with the respective control group. The differential expression of miRNA 342 in DM has been identified before, where the levels of several miRNAs, one of which was miRNA 342, were found to be differential among non‐glucose tolerant, T2D, and intermediate stages of impaired glucose tolerance …”
Section: Discussionmentioning
confidence: 87%